Engineering aspects of milk and dairy products - Coimbra, Jane Selia dos Reis , 1962-; Teixeira, Jose´ A. [ (Jose´ Anto´nio)] , 1957- (Contemporary food engineering, 2010)
Integrating the concepts of fluid flow, unit operations, and physical chemistry, this book addresses the engineering aspects of dairy products manufacturing. It discusses food safety and preservation as well as packaging and quality control. It also details a number of analysis methods, including spectroscopy, colorimetry, and polarimetry.